Cartoon Fables : Animal Symbolism in Kukryniksy’s Pravda Political Cartoons, 1965–1982 - Kangas, Reeta (fi=Turun yliopisto|en=University of Turku|, 2017)
Recent conflicts have highlighted that international and domestic propaganda campaigns, particularly in Russia, are once again becoming more significant. To understand this phenomenon, it is important to study the historical roots of propaganda in Russia, the tools and mechanisms that propagandists use to influence the political discourse. Animal symbolism is one of the most important of these tools. It is often used to belittle the enemy by describing their “non-human” nature. Furthermore, in using animals to depict negative characteristics of their enemies, propaganda also inadvertently builds upon and develops negative cultural stereotypes that are associated with those animals, thus creating a sort of feedback loop wherein the one strengthens the other. This dissertation examines the ways in which the famous Soviet propaganda artist trio Kukryniksy used animal symbolism in their political cartoons published during the rule of Leonid Brezhnev (1965—1982). The primary material of the research consists of 117 animal cartoons that were published in the Soviet Union’s main news source, Pravda. Methodologically and in its theoretical approach, this dissertation draws from a range of multidisciplinary fields, including Russian Studies, Propaganda Studies, Art History, and Human-Animal Studies. Its theoretical approach is largely based on frame theory and cartoon theory. The thesis is mainly based on qualitative methods. It relies on composition and discourse analysis, paying particular attention to how the cartoons worked within and reinforced preexisting cultural frameworks. There is also a quantitative element based around a content analysis of the frequency of various elements in the cartoons. The analysis of the frames Kukryniksy created and the techniques they used, shows that their animal symbols derived their significance from the animals’ proximity to the humans’ sphere of living, their behavioural traits, utilitarian functions, and linguistic and cultural nuances. With the use of culturally dependent references and different cartooning techniques, Kukryniksy constructed a framework in which the animal metaphor revealed the “true” nature of the enemy and taught the audience the moral of the story of international politics. As such, Kukryniksy’s political cartoons are part of a long tradition of Russian and Soviet propaganda that used animal symbolism to describe the enemy and divide the world into two spheres, “us” and “them”. By analysing this historical propaganda, this dissertation thus also helps us to better understand and deconstruct contemporary propaganda campaigns.

Viimeaikaisissa konflikteissa kansainvälisten ja kansallisten propagandakampanjoiden merkitys on korostunut ja tullut näkyvämmäksi; erityisesti huomion kohteena on ollut venäläinen propaganda. Venäläisen propagandan ymmärtämiseksi on tärkeää tutkia sen historiallisia juuria, sekä niitä välineitä ja mekanismeja, joilla propagandistit pyrkivät vaikuttamaan poliittiseen diskurssiin. Eläinsymboliikka on eräs merkittävä keino, jolla poliittiseen diskurssiin pyritään vaikuttamaan. Sitä käytetään vihollisen vähättelemiseen kuvaamalla tämä “epäinhimillisenä” olentona. Käyttämällä eläinsymboliikkaa propaganda ammentaa eläimiin liittyvistä negatiivisista kulttuurisista stereotypioista, samalla myös vahvistaen niitä. Näin syntyy eräänlainen itseään ruokkiva kehä, jossa propaganda ja stereotypiat vahvistavat toinen toistaan. Tämä väitöskirja tarkastelee kuuluisan neuvostoliittolaisen propagandataiteilijakolmikko Kukryniksyn tapoja käyttää eläinsymboleja pilakuvissaan Leonid Brežnevin hallintokauden (1965–1982) aikana. Tutkimuksen primaariaineisto koostuu 117 Pravdassa, Neuvostoliiton pääasiallisessa uutislähteessä, julkaistusta eläinpilakuvasta. Metodologiselta ja teoreettiselta pohjaltaan väitöskirja on monitieteellinen. Se asemoituu Venäjän tutkimuksen, propagandatutkimuksen, taidehistorian, sekä yhteiskunnallisen ja kulttuurisen eläintutkimuksen kenttään. Teoreettisina lähtökohtina toimivat kehysteoria ja pilakuvateoriat. Pääsääntöisesti tutkimus on kvalitatiivinen. Se tukeutuu rakenneanalyysiin ja diskurssianalyysiin. Erityisesti tarkastellaan pilakuvien toimintaa osana olemassa olevia viitekehyksiä sekä tapoja, joilla pilakuvat vahvistivat näitä viitekehyksiä. Tutkimuksessa on myös kvantitatiivisia, sisältöanalyysiin perustuvia tarkasteluja, joissa esitetään pilakuvien ja niissä esiintyneiden teemojen frekvenssejä. Kukryniksyn luomien kehysten ja käyttämien tekniikoiden analyysi paljastaa, että taiteilijakolmikon eläinsymbolien merkitykset kumpuavat pilapiirroksissa esiintyvien eläinten käyttäytymisestä, läheisyydestä ihmisten elinpiiriin, käyttötarkoituksista sekä kielellisistä ja kulttuurisista merkitysvivahteista. Kulttuurisidonnaisia viittauksia ja erilaisia pilakuvatekniikoita käyttäen Kukryniksy rakensi viitekehyksen, jossa eläinmetafora paljasti vihollisen “todellisen” luonteen ja pyrki samalla kertomaan lukijoille kansainvälisen politiikan takana piilevän moraalisen tarinan. Näin Kukryniksyn pilakuvat asemoituvat osaksi pitkää venäläisen ja neuvostoliittolaisen propagandan jatkumoa, joka käytti eläinsymboleita vihollisen kuvaamiseen ja maailman jakamiseen kahteen binääriseen kenttään, “meihin” ja “heihin.” Analysoimalla historiallista propagandaa tämä tutkimus auttaa paremmin ymmärtämään ja dekonstruoimaan yleisemminkin nykyaikaisia propagandakampanjoita.